Rethinking Race and Power in Design-Based Research: Reflections from the Field - Vakil, Sepehr; McKinney de Royston, Maxine; Suad Nasir, Na'ilah; Kirshner, Ben (Cognition and instruction, 2016)
Participatory design-based research continues to expand and challenge the "researcher" and "researched" paradigm by incorporating teachers, administrators, community members, and youth throughout the research process. Yet, greater clarity is needed about the racial and political dimensions of these collaborative research projects. In this article, we focus on how race and power mediate relationships between researchers and communities in ways that significantly shape the process of research. Using the notion of politicized trust as a conceptual lens, we reflect on two distinct participatory design projects to explore how political and racial solidarity was established, contested, and negotiated throughout the course of the design process. Ultimately, this article argues that making visible how race and power mediate relationships in design research is critical for engaging in ethical and sociopolitically conscious relationships with community partners and developing theoretical and practical knowledge about the repertoires of practice, tasks, and sociocultural competencies demanded of university researchers.